Armed Conflict in Central America and Immigrant Food Insecurity in the United States - Jeremy C. Green; Eric Adjei Boakye; Ellen K. Barnidge; Michael G. Vaughn (Springer, 2018)
Central American immigrants to the United States are a growing population with rates of food insecurity that exceed national averages. We analyzed multiple years of data from the Center for System Peace and the Current Population Survey, Food Security Survey Module, from 1998 to 2015. We used ordered probit and probit regressions to quantify associations between premigration residence in a country exposed to armed conflict in Central America and the food insecurity of immigrants in the United States. The study sample included 5682 females and 5801 males between the ages of 19 and 69 years who were born in Central America and migrated to the United States. The mean age of individuals included in the study sample was 38.2 years for females (standard deviation, 11.0) and 36.8 years for males (standard deviation, 10.6). Premigration armed conflict was associated with a 10.7% point increase in postmigration food insecurity among females (95% confidence interval, 6.8-14.5), and a 9.5% point increase among males (95% confidence interval, 5.0-14.0).